ANALISIS FAKTOR PENYEBAB GANGGUAN MUSKULOSKELETAL PADA PEKERJA DI PABRIK FERONIKEL BAGIAN SMELTING PT. ANEKA TAMBANG (PERSERO) TBK UNIT BISNIS PERTAMBANGAN NIKEL SULAWESI TENGGARA - , Syawal K. Saptaputra ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. Occupational disease is being a concern in the world of employment. Occupational disease could affects effectiveness and efficiency of a worker that will ultimately lead to decreased employeeâs productivity. Musculoskeletal disorder is one of the occupational disease that become a trend over the last few years in PT. Antam (Persero) UBPN Southeast Sulawesi. Objective. This study aim is to determine factor that can cause musculoskeletal disorder in smelting section factory workers PT. Antam (persero) UBPN Southeast Sulawesi Method. This study was observational analytic study using a cross sectional design. The number of research subject were 56 people. Independent variables were age, years of smoking, and occupational stress. The dependent variable was musculoskeletal disorder. Variable measurement of age, length of work, and smoking habit were using questionnaire of respondent identity. Occupational stress measurement was using job stress indicator questionnaire. Musculoskeletal disorder measurement was using Nordic Body Map questionnaires, followed by lactic acid level examination by lactate oxidase-colorimetric method. Result. The result of lactic acid level of 8 respondent, there were 2 respondents who had lactic acid level exceed the reference value. Lactic acid levels of respondent 2 was 2.74 mmol/L and respondent 7 was 2.70 mmol/L, and for the other 6 respondent were in the range of reference value. Reference value of lactic acid level started from 0.5 to 2.2 mmol/L. Multivariate analysis showed a correlation coefficient (R) of 0,593, R2 = 0,352, regression F value = 9,412 and p = 0.000, it can be concluded that there is a significant relationship (p < 0.05) together factors of age (p = 0,002), occupational stress (p=0,014), and smoking (p = 0,008). Conclusion. There was significant relationship between age, occupational stress, and smoking with musculoskeletal disorders. There was no significant effect between length of work and lactic acid level with musculoskeletal disorder Keywords. Musculoskeletal Disorders, Ferronickel Workers, Nordic Body Map, Occupational Stress Quest.